Evolution of craniofacial shape in relation to sexual dimorphism in Theropithecus and Papio - Ossorio, Ángeles; Figueroa-Torrejón, Ambra; Buston, Rodrigo; Caldon, Matteo; Mathe, Jacinto; Doria, Giuliano; Gippoliti, Spartaco; Volta, Antonella; Ferreira da Silva, María Joana; Bobe, René; Carvalho, Susana; Capelli, Cristian; et al. (Frontiers in Ecology and Evolution, 2025)
IntroductionSexual dimorphism in cranial morphology is a significant aspect of primate evolution, providing insights into evolutionary pressures and mating systems in different species. This study focuses on cranial sexual dimorphism in Papio and Theropithecus, two closely related genera within the tribe Papionini. MethodsUsing geometric morphometric techniques, we analyzed 570 cranial specimens from both genera, with data sourced from various studies and repositories. Thirty craniofacial landmarks were defined and analyzed through Geometric Morphometrics tools to evaluate shape variation. ResultsOur findings reveal distinct morphological clusters for each genus and sex, with Papio and Theropithecus exhibiting significant sexual dimorphism. The results distinguish genera and sex-based groups, indicating differential impacts of size on shape across groups. The findings suggest that while sexual dimorphism is stable in magnitude within each genus, the specific morphological manifestations differ. DiscussionThis research advances our understanding of the evolutionary mechanisms driving sexual dimorphism and emphasizes the need for further studies to explore the genetic and environmental factors influencing these differences. The innovative approach and comprehensive dataset provide a robust framework for future investigations into primate cranial morphology and its evolutionary implications.